Design of high performance p-type sensitizers with pyridinium derivatives as the acceptor by theoretical calculations - Sun, Zhi-Dan; Zhao, Jiang-Shan; Ayyanar, Karuppasamy; Ju, Xue-Hai; Xia, Qi-Ying (RSC advances, 2020)
Based on triphenylamine as an electron donor and thiophene as a π-linker, Series P and A p-type sensitizers were designed to investigate the effects of the different acceptors on the properties of the sensitizers. The optimized molecular structures, electronic and optical properties were investigated by density functional theory (DFT) and time-dependent DFT (TD-DFT). The results showed that the properties of the dyes can be tuned by the introduction of the different electron-withdrawing groups to the N atom in the pyridinium acceptor. Compared with the synthesized Series P dyes used in p-type sensitizers, the properties of Series A dyes, except for two dyes that cannot be used as p-type sensitizers, are improved by means of modifying pyridinium acceptors. Due to the suitable electron-withdrawing ability of the hexafluorodiacetylamino group in its acceptor, A6 has the narrowest energy gap (1.90 eV), the largest driving force of hole injection (Δ G inj , −0.68 eV), the high light harvesting efficiency (LHE, 0.9984) and the smallest internal reorganization energy ( λ int , 5.05 kcal mol −1 ). Hence, A6 not only enhances electronic excitation, but also improves the reorganization energy. Importantly, A6 shows the largest red shift and the maximum integral values of the adsorption over the visible light, as well as the strongest adsorption energy (−74.80 kcal mol −1 ) on a NiO surface. Thus, A6 may be a promising sensitizer for the p-type dye-sensitized solar cells (DSSCs), and the acceptor of A6 may provide a new and easily accessible high performance acceptor for p-type sensitizers. Based on triphenylamine as an electron donor and thiophene as a π-linker, Series P and A p-type sensitizers were designed to investigate the effects of the different acceptors on the properties of the sensitizers.